2019
DOI: 10.1002/jcp.28816
|View full text |Cite
|
Sign up to set email alerts
|

The small molecule SI113 hinders epithelial‐to‐mesenchymal transition and subverts cytoskeletal organization in human cancer cells

Abstract: The small molecule SI113 is an inhibitor of the kinase activity of SGK1, a key biological regulator acting on the PI3K/mTOR signal transduction pathway. Several studies demonstrate that this compound is able to strongly restrain cancer growth in vitro and in vivo, alone or in associative antineoplastic treatments, being able to elicit an autophagic response, either cytotoxic or cytoprotective. To elucidate more exhaustively the molecular mechanisms targeted by SI113, we performed activitybased protein profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
(85 reference statements)
1
17
0
Order By: Relevance
“…In particular, compound 4 was able to halve E. coli bacterial growth (Figure 4) at the lowest concentration tested (50 µg/mL). For compounds 2 (SI113) and 3, which here showed comparable antimicrobial activity against both the bacterial strains, we have previously reported their anticancer activity in vitro and in vivo [27,35] (as discussed above). Interestingly, the SI113-dependent inhibition of SGK1 was also demonstrated to enhance cytotoxic autophagy in GBM cell lines, leading to cancers cell death [30].…”
Section: Biological Activitiessupporting
confidence: 53%
See 1 more Smart Citation
“…In particular, compound 4 was able to halve E. coli bacterial growth (Figure 4) at the lowest concentration tested (50 µg/mL). For compounds 2 (SI113) and 3, which here showed comparable antimicrobial activity against both the bacterial strains, we have previously reported their anticancer activity in vitro and in vivo [27,35] (as discussed above). Interestingly, the SI113-dependent inhibition of SGK1 was also demonstrated to enhance cytotoxic autophagy in GBM cell lines, leading to cancers cell death [30].…”
Section: Biological Activitiessupporting
confidence: 53%
“…Our preliminary study in an antimicrobial context revealed the strong antibacterial potential of pyrazolo [3,4-d]pyrimidines already active as kinase inhibitors [35,45] and endowed with antiproliferative properties. In particular, six compounds were identified for their bacteriostatic activity against Gram-positive S. aureus and Gram-negative E. coli.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, a new inhibitor for SGK1, named SI113, has been developed. In cellular models as well as in murine models, SI113 has amply demonstrated potential antineoplastic capacity, showing a very low toxicity profile ( Abbruzzese et al, 2017 , 2019 ; Catalogna et al, 2017 ; Matteoni et al, 2019 ). Pharmacological ADME (absorption, distribution, metabolism, and excretion) studies have corroborated the ability of SI113 to cross the blood-brain barrier, thus opening the possibility of a rational use of the molecule, even in psychiatric and neurological diseases ( Talarico et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of SGK1 decreases the mesenchymal markers N-cadherin, vimentin, and focal adhesion kinase, and reduces the cell motility and invasion abilities. 18 As noted previously, mAR demonstrates strong antioxidant and antitumorigenic effects, which are mediated by vinculin phosphorylation and actin reorganization. Transfection with a constitutively active SGK1 mutant effectively dephosphorylates the cell-adhesion protein vinculin and enhances cell motility.…”
Section: Functions and Mechanisms Of Sgk1 In Oncologymentioning
confidence: 66%
“… 1 , 3 , 14 , 15 SGK1 has been previously reported in hypertension, diabetes, hypercoagulability, and autoimmune disease. 5 , 16 , 17 A growing number of recent studies reveal a role for SGK1 in human tumors such as glioblastoma, 18 20 breast, 21 25 colorectal, 26 28 prostate, 29 31 thyroid, 32 ovarian, 33 myeloma, 11 and non-small cell lung cancer 34 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%